Citizens’ initiative for connected healthcare in the Netherlands: a case study using semi-structured interviews - Jeffrey Bouwmeester; Marianne Dees; Kirsten Bevelander; Sietske Grol; Taco Brandsen; Maria van den Muijsenbergh (Discover Public Health)
Abstract Background A broad governance trend encouraging citizens to take greater responsibility for their health has led to an increased need for Citizen Initiatives (CI)s in healthcare and welfare. These initiatives utilize informal and formal resources and networks to deliver healthcare and often interact with local governments through collaborative forms such as co-creation. Despite its potential, co-creation in healthcare remains relatively underexplored. Methods Using a qualitative design, we investigated the perspectives of key stakeholders of a healthcare CI and a municipal government to increase and informalize health and welfare through reablement. Results We show that the CI collaboration centres on three main themes: (1) creating a shared CI vision, (2) capacity of citizens and municipal workers to collaborate, and (3) addressing elements required for a sustainable collaboration. Mechanisms of control, municipal boundary setting, and opaque decision-making were regarded as factors hindering collaboration. In contrast, commitment, understandable communication, boundary crossing social capital, and political support are considered important CI collaboration facilitators. Conclusions To conclude, healthcare and welfare CI and municipality co-creations benefit from a clear and shared vision and methods, empowered stakeholders, and mitigated power imbalances. Future studies should develop new accountability structures and safeguards for citizens with limited participation abilities, especially when municipalities participate in health or welfare CIs.